2022
DOI: 10.3390/gels8050275
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells–Hydrogel Microspheres System for Bone Regeneration in Calvarial Defects

Abstract: The repair of large bone defects in clinic is a challenge and urgently needs to be solved. Tissue engineering is a promising therapeutic strategy for bone defect repair. In this study, hydrogel microspheres (HMs) were fabricated to act as carriers for bone marrow mesenchymal stem cells (BMSCs) to adhere and proliferate. The HMs were produced by a microfluidic system based on light-induced gelatin of gelatin methacrylate (GelMA). The HMs were demonstrated to be biocompatible and non-cytotoxic to stem cells. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…76 Additionally, microfluidic technology has been employed to create GelMA hydrogel microspheres (HMs) for bone regeneration. 77 Teng et al fabricated GelMA HMs to treat calvarial defects in rats. The microspheres were found to have a size of 282.92 ± 3.82 μm and a stiffness of 2.28 kPa.…”
Section: Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Additionally, microfluidic technology has been employed to create GelMA hydrogel microspheres (HMs) for bone regeneration. 77 Teng et al fabricated GelMA HMs to treat calvarial defects in rats. The microspheres were found to have a size of 282.92 ± 3.82 μm and a stiffness of 2.28 kPa.…”
Section: Mscsmentioning
confidence: 99%
“…Injecting seeded microspheres into rat calvarial defects resulted in higher bone formation compared to the groups treated with microspheres without cells and the untreated group (Figure 5D). 77 The casting method is a cost-effective and straightforward approach for generating gels used in tissue engineering as it does not necessitate sophisticated equipment. Moreover, this method is not constrained by considerations such as shear thinning behavior or printability, which are significant in more intricate techniques.…”
Section: Mscsmentioning
confidence: 99%
“…For example, MSCs cultured in the hydrogels of gelatin methacrylate (GelMA) stimulate osteogenic differentiation of MSCs. 54 Hence, tissue-derived materials like decellularized ECM, hyaluronic acid, chondroitin sulfate, collagen, fibronectin, and alginate are the preferred choices for tissue regeneration approaches. Natural scaffold materials possess more cell affinity and less cytotoxicity due to their degraded products and naturally carry cell attachment sites.…”
Section: Microenvironmental Cuesmentioning
confidence: 99%
“…8 Other studies confirmed that the cell/hydrogel system could promote bone formation in calvarial defects and segmental bone defects. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…8 Other studies confirmed that the cell/ hydrogel system could promote bone formation in calvarial defects and segmental bone defects. 9,10 Although a number of studies have detailed the cell delivery with hydrogels, 11,12 few studies have focused on the effect of pre-osteogenic differentiation on the in vivo osteogenesis for cell/hydrogel constructs, and the results are mixed. Corn et al prepared undifferentiated MSCs, which were encapsulated into alginate hydrogel and were implanted into bone defects immediately.…”
Section: Introductionmentioning
confidence: 99%